2006
DOI: 10.1177/1466424006063184
|View full text |Cite
|
Sign up to set email alerts
|

A staged screening strategy for prenatal alcohol exposure and maternal risk stratification

Abstract: This screening process has very modest time commitments in the early stages. Time commitments increase for women drinking during pregnancy and the process focuses on the population at highest risk of having a child with FASD. The process has the benefit of risk specificity, since the process refines risk estimates for an adverse outcome specific for FASD. The process concludes with a programme to facilitate intervention and to monitor changes in prenatal alcohol exposure during pregnancy. Prevention of FASD is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Alternatively, the use of risk stratification strategies to identify women at increased levels of risk may further increase statistical options . In addition to data on smoking, other useful indicators of risk include previous substance abuse treatment of all types (alcohol is often used in combination with other drugs), current substance abuse for all types of drugs, late or no prenatal care, low levels of educational achievement, previous sibling with a diagnosis of FASD, previous infant or child death, increased maternal age, and a family history of female relatives with a history of alcohol abuse (Abel, 1998;Burd et al, 2006). Including alcohol screening questionnaires and using blood biomarkers could be of some value as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the use of risk stratification strategies to identify women at increased levels of risk may further increase statistical options . In addition to data on smoking, other useful indicators of risk include previous substance abuse treatment of all types (alcohol is often used in combination with other drugs), current substance abuse for all types of drugs, late or no prenatal care, low levels of educational achievement, previous sibling with a diagnosis of FASD, previous infant or child death, increased maternal age, and a family history of female relatives with a history of alcohol abuse (Abel, 1998;Burd et al, 2006). Including alcohol screening questionnaires and using blood biomarkers could be of some value as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies for early detection of alcohol use during pregnancy are available (ACOG Committee, 2004;Burd et al, 2006;Chang, 2001). However, none has adequate epidemiologic performance criteria to be recommended as a single strategy that is optimal across populations and in multiple settings.…”
Section: Introductionmentioning
confidence: 99%
“…An Alberta study found that while 50% of women reported alcohol consumption pre-pregnancy recognition, 18% continued to drink even after post-pregnancy recognition [21]. A review of the Canadian literature, while somewhat lacking, supports this and overall, Canadian rates of maternal alcohol consumption during pregnancy are comparable with those of the U.S., estimated between 5-15% [19,22-25]. Worldwide rates are variable, with other nations including Australia and many European countries reporting higher prevalence [6,8,26].…”
Section: Introductionmentioning
confidence: 98%
“…Regardless, many women continue to consume alcohol to various degrees throughout their pregnancies. This is a problem in much, if not all, of the world [19]. It appears from the published data on women's gestational consumption of alcohol that Canadian and U.S. rates have generally been declining since the 1990's.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of childbearing age or pregnant women is the only approach to primary prevention of FASD (58)(59). Screening methods focusing on infants or children with FAS have also been developed.…”
Section: Screening For Fasmentioning
confidence: 99%